Necroptosis induced by RIPK3 requires MLKL but not Drp1 - Moujalled, D M (Nature Publishing Group, 2014)
Necroptosis is a mechanism by which cells can kill themselves that does not require caspase activity or the presence of the pro-apoptotic Bcl-2 family members Bax or Bak. It has been reported that RIPK3 (receptor interacting protein kinase 3) activates MLKL (mixed lineage kinase domain-like) to cause cell death that requires dynamin-related protein 1 (Drp1), because survival was increased in cells depleted of Drp1 or treated with the Drp1 inhibitor mdivi-1. To analyze necroptosis in a system that does not require addition of tumor necrosis factor (TNF), we used a construct that allows RIPK3 to be induced in cells, and then dimerized via an E. coli gyrase domain fused to its carboxyl-terminus, using the dimeric gyrase binding antibiotic coumermycin. We have previously shown elsewhere that RIPK3 dimerized in this manner not only induces necroptosis but also apoptosis, which can be inhibited by the broad-spectrum caspase inhibitor Q-VD-OPh (QVD). In response to RIPK3 dimerization, wild-type mouse embryonic fibroblasts (MEFs) underwent cell death that was reduced but not completely blocked by QVD. In contrast, death upon dimerization of RIPK3 in Mlkl(−/−) MEFs was completely inhibited with QVD, confirming that MLKL is required for necroptosis. Similar to wild-type MEFs, most Drp1(−/−) MEFs died when RIPK3 was activated, even in the presence of QVD. Furthermore, overexpression of wild-type MLKL or dominant active mutants of MLKL (Q343A or S345E/S347E) caused death of wild-type and Drp1(−/−) MEFs that was not inhibited with QVD. These results indicate that necroptosis caused by RIPK3 requires MLKL but not Drp1.